Investigating the Performance of Laplacian Operator on Digital Images in Spatial Domain - Hassand, Allah Mohammad (Journal of Natural Sciences – Kabul University, 2023)
The Laplacian operator is used as a filter on digital images. Laplacian-based filters are employed to enhance digital images. These filters' features for image enhancement include image sharpening, detecting fine details, and edge detection. The Laplacian is a linear operator, so the implementation of these filters is straightforward in the spatial domain. These filters can also be applied for non-linear filtering. Spatial domain processing methods are computationally efficient, requiring fewer processing resources, making Laplacian-based filters cost-effective for electronic devices in terms of computation and processing. In this paper, spatial linear filters based on the Laplacian are designed and implemented on various images using MATLAB software. The results demonstrate that Laplacian-based filters improve image quality and show better performance.